1954
DOI: 10.1038/icb.1954.37
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Lysis of Erythrocytes Treated With Staphylococcal Β Toxin

Abstract: The action of staphylococcal /8 toxin on the erythrocytes of a number of species of animal was described by Bryce and Rountree (1936). These workers found that when the j8 toxin was mixed with the erythrocytes of certain species and the mixture held at 37° C. for one hour there was no lysis, but if it was then transferred to the cold the cells lysed. Christie, Atkins and Munch-Petersen (1944) showed that this lysis could be completed in ruminant erythrocytes at 37° C. by the action of a factor produced during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1959
1959
1984
1984

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…However, SO produced in broth cultures is never entirely oxidized, and some activity is present even in the absence of reducing agents (11). Sphingomyelinase-depleted SRBC (f-SRBC) are highly susceptible to lysis by a wide variety of physical, chemical, and biological agents (14) and are also more liable to lysis by SO than SRBC not exposed to staphylococcal sphingomyelinase (Table 1). It would seem that the SO produced by group A streptococci in the CAMP test system has sufficient activity to lyse the fragile 3-SRBC used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SO produced in broth cultures is never entirely oxidized, and some activity is present even in the absence of reducing agents (11). Sphingomyelinase-depleted SRBC (f-SRBC) are highly susceptible to lysis by a wide variety of physical, chemical, and biological agents (14) and are also more liable to lysis by SO than SRBC not exposed to staphylococcal sphingomyelinase (Table 1). It would seem that the SO produced by group A streptococci in the CAMP test system has sufficient activity to lyse the fragile 3-SRBC used.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the staphylococcal beta-lysin is a sphingomyelinase (9) which depletes the erythrocyte membrane of lipids, making the erythrocytes susceptible to subsequent lysis by a variety of physical, chemical, or biological agents. These agents include mechanical damage, temperature or pH changes, and EDFA as well as the CAMP factor of GBS (14,16). The extracellular CAMP factor is now known to be a thermostable protein with a molecular weight of 23,500 and the ability to lyse beta-lysin-sensitized, but not intact, SRBC (1).…”
mentioning
confidence: 99%
“…Further, the requirements for optimal CAMP factor production (12), in particular pH, peptone, and carbohydrate content, must be met by the same medium. In addition, even in the absence of CAMP factor, physical factors, including alterations in temperature, pH, and osmolarity, may induce lysis of the beta-lysin-affected sheep RBC (11,16). This multiplicity of variables helps to explain the vagaries of CAMP tests, without even considering the problems of lysis due to non-group B streptococci.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cells do not lyse unless a further condition is imposed upon the system. The additional requirement can be met in a variety of ways, as by chilling (5), addition of ethylenediaminetetraacetate (22), alteration of pH or salt concentration (20,25), or addition of a specific extracellular product of streptococci belonging to Lancefield group B (Streptococcus agalactiae) (8). The last agent provides the basis for a laboratory test for the presumptive identification of group B streptococci, used in veterinary microbiology since the pioneering work of Christie et al in 1944 (8).…”
mentioning
confidence: 99%